Characterising deep vadose zone water movement and solute transport under typical irrigated cropland in the North China Plain. Issue 7 (15th February 2017) - Min, Leilei; Shen, Yanjun; Pei, Hongwei; Jing, Bingdan
Abstract: Understanding the dynamics and mechanisms of soil water movement and solute transport is essential for accurately estimating recharge rates and evaluating the impacts of agricultural activities on groundwater resources. In a thick vadose zone (0–15 m) under irrigated cropland in the piedmont region of the North China Plain, soil water content, matric potential, and solute concentrations were measured. Based on these data, the dynamics of soil water and solutes were analysed to investigate the mechanisms of soil water and solute transport. The study showed that the 0–15‐m vadose zone can be divided into three layers: an infiltration and evaporation layer (0–2 m), an unsteady infiltration layer (2–6 m), and a quasi‐steady infiltration layer (6–15 m). The chloride, nitrate, and sulphate concentrations all showed greater variations in the upper soil layer (0–1 m) compared to values in the deep vadose zone (below 2 m). The average concentrations of these three anions in the deep vadose zone varied insignificantly with depth and approached values of 125, 242, and 116 mg/L. The accumulated chloride, sulphate, and nitrate were 2, 179 ± 113, 1, 760 ± 383, and 4, 074 ± 421 kg/ha, respectively. The soil water potential and solute concentrations indicated that uniform flow and preferential flow both occurred in the deep vadose zone, and uniform flow was the dominant mechanism of soil water movement in this study. The piston‐like flow velocity of solute transport was 1.14 m per year, and the average value of calculated leached nitrate nitrogen was 107 kg/ha∙year below the root zone. The results can be used to better understand recharge processes and improve groundwater resources management.